2009
DOI: 10.1093/jac/dkp050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term trimethoprim/sulfamethoxazole treatment on resistance and integron prevalence in the intestinal flora: a randomized, double-blind, placebo-controlled trial in children

Abstract: Initially, trimethoprim/sulfamethoxazole usage was strongly associated with the appearance of integron-positive (multi)drug-resistant Enterobacteriaceae in the intestinal flora. After prolonged exposure to trimethoprim/sulfamethoxazole, however, this population of Enterobacteriaceae was substituted by a population with non-integron-associated resistance mechanisms. After trimethoprim/sulfamethoxazole was discontinued, susceptibility rates to all antibiotics returned to baseline levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Bands 5 and 12 revealed slight changes in healthy fish gut after the antibiotic treatment, both bands showing high similarities to Enterobacteriaceae. Van der Veen et al (2009) found that trimethoprim/sulfamethoxazole was closely associated with the appearance of (multi)drugresistant Enterobacteriaceae in child intestinal flora. Enterobacteriaceae might be the major drug-resistant bacteria in gibel carp intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Bands 5 and 12 revealed slight changes in healthy fish gut after the antibiotic treatment, both bands showing high similarities to Enterobacteriaceae. Van der Veen et al (2009) found that trimethoprim/sulfamethoxazole was closely associated with the appearance of (multi)drugresistant Enterobacteriaceae in child intestinal flora. Enterobacteriaceae might be the major drug-resistant bacteria in gibel carp intestine.…”
Section: Discussionmentioning
confidence: 99%
“…78 Clearly, the host environment as well as the antibiotic treatment are likely to be influencing integron transfer on MGEs, a similar situation as seen with ICEs. 60 An interesting observation by van der Veen et al 102 was that the prevalence of integrons within the intestinal microbial populations decreased despite continued antibiotic treatment. This may indicate that there is a cost to the bacteria of carrying either the integron or its shuttle element.…”
mentioning
confidence: 99%
“…3B). Hochut et al 107 found that an SXT conjugative element is embedded within rumB in V. cholera and suggested that a transposon had inserted into the DNA and intestines of humans and chickens showed that there may be a correlation in acquisition based on treatment with antibiotics 102 although another study suggested this is not the case. 78 Clearly, the host environment as well as the antibiotic treatment are likely to be influencing integron transfer on MGEs, a similar situation as seen with ICEs.…”
mentioning
confidence: 99%
“…Children receiving TMP/SMX were found to have higher rates of multidrug-resistant Enterobacteriaceae in their intestinal flora compared to placebotreated children, possibly through selection of an integron carrying multiple resistance genes (33). However, a recent systematic review did not find a relationship between TMP/SMX prophylaxis and other resistant microbial flora in patients with HIV infection (29).…”
mentioning
confidence: 99%